Harvey Cushing's Early Operative Treatment of Skull Base Fractures - Pendleton, Courtney; Raza, Shaan M.; Gallia, Gary L.; Quinones-Hinojosa, Alfredo (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objectives To review Dr. Harvey Cushing's early surgical cases at the Johns Hopkins Hospital, revealing details of his operative approaches to fractures of the skull base.Design Following institutional review board approval and through the courtesy of the Alan Mason Chesney Archives, we reviewed the Johns Hopkins Hospital surgical files.Setting The Johns Hopkins Hospital, 1896 to 1912.Participants A total of 24 patients underwent operative treatment for suspected fractures of the skull base.Main Outcome Measures The main outcome measure was operative approach, postoperative mortality, and condition recorded at the time of discharge.Results Overall, 23 patients underwent operative treatment for suspected skull base fractures. The mechanisms of injury were known for 22 patients and included work-related injuries (41%), falls (23%), vehicle injuries (32%), and other trauma (5%). One patient had no mechanism of injury specified in the file. The outcome at the time of discharge from the hospital was “well” or “improved” in 12 patients (52%). The remaining 11 patients died during their admission.Conclusions Although Cushing's experience with selected skull base pathology has been previously reported, the breadth of his contributions to operative approaches to the skull base has been neglected.
Keywords: Harvey Cushing; skull base; trauma; fracture